121 Overdiagnosis by conducting cancer screening other than guidelines in japan. (20th August 2018) - Takahashi, Hirokazu; Machii, Ryoko; Matsuda, Kazuko; Saika, Kumiko; Nakayama, Tomio
Abstract : Objectives: Although cancer screening guidelines are indicated from Ministry of Health, Labour and Welfare to municipalities and municipalities implement for residents, however overdiagnosis due to increase not based on the guidelines is increasing.To examine overdiagnosis by conducting cancer screening other than guidelines. Method: Based on a questionnaire survey conducted by the Ministry of Health, Labor and Welfare, calculate the cancer screening execution rate other than the guidelines and compare and investigate incidence and mortality rates of each cancer based on regional cancer registration data in time series. Results: Municipalities performing breast ultrasonography increased from 21.2% to 31.9%, PSA examination increased from 42.1% to 91.7% between 2006 to 2013. During the same period, age adjusted incidence of breast cancer was 60.3 to 85.6 (per 100, 000), mortality rate was 8.9 to 9.1, incidence of prostate cancer was 28.2 to 41.4, and mortality rate was 5.3 to 4.8 respectively. Conclusions: As breast ultrasonography and PSA examination spread, overdiagnosis of breast cancer and prostate cancer was increased in Japan.